2007
DOI: 10.1007/s10493-007-9076-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental method for isolating and identifying dust mites from sputum in pulmonary acariasis

Abstract: The aim of this study was to pilot a simpler and more effective method for identifying dust mites in sputum. Dust mites and their allergens have been implicated in respiratory diseases, including pulmonary acariasis, and several studies have identified mites in sputum. Further research is dependent on the development of a faster and simpler diagnostic test. We have demonstrated that dust mites artificially introduced into sputa, could be identified after the sputa were liquefied with bleach, when the liquid sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Further, in 2007 a new process for identifying mites in sputum was developed. Martínez-Girón R et al [23] demonstrated that dust mites artificially introduced into sputa could be identified after sputa were liquified with bleach and the liquid sample was observed under the microscope. Their approach offers a time- and cost-saving tool for identifying dust mites in sputum, but the test is not commonly applied in the clinic because acariasis is not well recognized.…”
Section: Reviewmentioning
confidence: 99%
“…Further, in 2007 a new process for identifying mites in sputum was developed. Martínez-Girón R et al [23] demonstrated that dust mites artificially introduced into sputa could be identified after sputa were liquified with bleach and the liquid sample was observed under the microscope. Their approach offers a time- and cost-saving tool for identifying dust mites in sputum, but the test is not commonly applied in the clinic because acariasis is not well recognized.…”
Section: Reviewmentioning
confidence: 99%